The Formation of Political Persuasion: a Philosophical Analysis - Avazovich, Shernazarov Ravshan (Indonesian Journal Publisher, 2024)
This article theoretically analyzes the essence of the concept of political faith and the basis of important processes and trends in the political, social and cultural spheres of modern society. At the same time, in today’s era of globalization, it is thought that only a person with a strong political persuasion can understand the meaning and essence, causes and consequences of various processes, and only a person with a fully settled political persuasion can be an active participant in the processes taking place in the social space.